Hubungan Leader Member Exchane Dan TurnOver Intention Yang Dimediasi Oleh Organization Identification - Sari, Raditya Purnama; puspa, Tiara (Manajemen Bisnis Kompetensi, 2017)
This study aims to analyze the relationship of leader member exchange on organization identification and turnover intention. Data in this study able to collect 100 questionnaires to all employees at PT Mitra Powerindo Sejahterah Jakarta. Research tools used is Structural Equation Modeling. This study found the relationship between the leader member exchange and turnover intention is mediated by organizational identification. The better leader member exchange and supported by organizational identification, will reduce the employee intent to commit turnovers.Keywords: leader member ex-change; organization identification; turnover intention